Respuesta :

For this case we have the following equation:

[tex]25^{x} = 5^{ x^2-3}[/tex]

Rewriting we have:

[tex]5^{2 (x)} = 5^{ x^ 2-3}\\5^{ 2x} = 5^{ x^ 2-3}[/tex]

For expressions to be equal, exponents must be equal. So:

[tex]2x = x ^ 2-3\\x ^ 2-2x-3 = 0[/tex]

To factor, we look for two numbers that, when multiplied, result in -3 and when added, result in -2. These numbers are -3 and 1.

[tex](x-3) (x + 1) = 0[/tex]

Thus, the roots are:

[tex]x_ {1} = 3\\x_ {2} = - 1[/tex]

Answer:

[tex]x_ {1} = 3\\x_ {2} = - 1[/tex]

its

x = –1, x = 3

Step-by-step explanation:

edge2020